Impact of the Coronavirus Disease 2019 Pandemic on an Emergency Department Service: Experience at the Largest Tertiary Center in Taiwan - Tsai LH; Chien CY; Chen CB; Chaou CH; Ng CJ; Lo MY; Seak CK; Seak JCY; Goh ZNL; Seak CJ (Dove Medical Press, 2021)
Li-Heng Tsai,1,2 Cheng-Yu Chien,1– 3 Chen-Bin Chen,1,2,4 Chung-Hsien Chaou,1,2 Chip-Jin Ng,1,2 Mei-Yi Lo,5 Chen-Ken Seak,6 Joanna Chen-Yeen Seak,6 Zhong Ning Leonard Goh,6 Chen-June Seak1,2,4,7 1Department of Emergency Medicine, Lin-Kou Medical Center, Chang Gung Memorial Hospital, Taoyuan, Taiwan; 2College of Medicine, Chang Gung University, Taoyuan, Taiwan; 3Department of Emergency Medicine, Ton-Yen General Hospital, Zhubei, Taiwan; 4Department of Emergency Medicine, New Taipei Municipal Tucheng Hospital, New Taipei City, Taiwan; 5Department of Nursing, Lin-Kou Medical Center, Chang Gung Memorial Hospital, Taoyuan, Taiwan; 6Sarawak General Hospital, Kuching, Sarawak, Malaysia; 7Center for Quality Management, New Taipei Municipal Tucheng Hospital, New Taipei City, TaiwanCorrespondence: Chen-June SeakDepartment of Emergency Medicine, Lin-Kou Medical Center, Chang Gung Memorial Hospital, No. 5, Fusing St., Guei-Shan Township, Taoyuan County 333, TaiwanTel +886-3-3281200 ext. 5235Fax +886-3-3287715Email julianseak@hotmail.comPurpose: Severe Acute Respiratory Syndrome coronavirus 2 (SARS-CoV-2) is an emerging contagious pathogen that has caused community and nosocomial infections in many countries. This study aimed to evaluate the impact of Coronavirus disease 2019 (COVID-19) on emergency services of the largest medical center in Taiwan by comparing emergency department (ED) usage, turnover, and admission rates before the COVID-19 outbreak with those during the outbreak.Materials and Methods: A retrospective cohort study was conducted in the ED of the largest tertiary medical center in Taiwan. Trends of adult, non-trauma patients who visited the ED during February–April 2019 were compared with those during February–April 2020. The number of visits, their dispositions, crowding parameters, and turnover rates were analyzed. The primary outcome was the change in ED attendance between the two periods. The secondary outcomes were changes in hospital admission rates, crowding parameters, and turnover rates.Results: During the outbreak, there were decreased non-trauma ED visits by 33.45% (p < 0.001) and proportion of Taiwan Triage and Acuity Scale (TTAS) 3 patients (p=0.02), with increased admission rates by 4.7% (p < 0.001). Crowding parameters and turnover rate showed significant improvements.Conclusion: Comparison of periods before and during the COVID-19 outbreak showed an obvious decline in adult, non-trauma ED visits. The reduction in TTAS 3 patient visits and the increased hospital admission rates provide references for future public-health policy-making to optimise emergency medical resource allocations globally.Keywords: emergency department, Coronavirus disease 2019, Taiwan Triage and Acuity Scale, Stratification to Prevent Overcrowding Taskforce, SPOT